MOTILITY INDUCTION OF Salmonella pullorum UNDER MODIFIED CONDITIONS IN SUDAN (Journal of Veterinary Medicine and Animal Production, 2022)
Motility of Salmonella pullorum under modified condition in Sudan was performed by modifying the growth conditions. Semisolid medium instead of the usually used solid motility medium consist of 53g gelatin, 25g heart infusion broth and 2 g agar supplemented with 0.5% dextrose was used. Incubation temperature was raised increased from37Co to 42,5Co and the duration of incubation was increased from 24hr to 48hrs. For testing the motility, imported Salmonella pullorum ( Health Protection Agency Culture Collection, UK Taxonomy Tax Link: S9096)) was purchased and a local strain of Salmonella eneritidis isolated from Rabak Veterinary Research Laboratory was used as positive control. Diffusion line which indicated movement in the positive control Salmonella enteritidis inoculated tube as well as in the other tube inoculated with Salmonella pullorum was observed. Those lines were seen more clearly at 42,5Co and incubation temperature for 48 hrs. These diffusion lines indicated that Salmonella pullorum can exhibit the ability of possessing flagellae and, hence motility.